2020
DOI: 10.1007/s10452-020-09781-x
|View full text |Cite
|
Sign up to set email alerts
|

Do the ecological drivers of lake littoral communities match and lead to congruence between organism groups?

Abstract: Lake littoral environments are heterogeneous, and different organisms typically show specific responses to this environmental variation. We examined local environmental and spatial factors affecting lake littoral biodiversity and the structuring of assemblages of phytoplankton, zooplankton and macroinvertebrates within and among three basins of a large lake system. We explored congruence of species composition and species richness among the studied organism groups to evaluate their general indicator potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…There is a rich body of ecological literature which explored the congruence of patterns between taxonomic groups as indicators of environmental change and ecological status (e.g. [ 64 ]), which suggested that weak congruence between results from different ecological communities requires multiple lines of evidence to help strengthen the inference [ 65 67 ]. Given that monitoring lakes to the extent done in the Swedish lakes monitoring program is extremely costly, our results suggest that measuring either phytoplankton or the physicochemical environment may lead to similar results about spatial and temporal variability in the lake landscape; thereby, substantially reducing monitoring costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a rich body of ecological literature which explored the congruence of patterns between taxonomic groups as indicators of environmental change and ecological status (e.g. [ 64 ]), which suggested that weak congruence between results from different ecological communities requires multiple lines of evidence to help strengthen the inference [ 65 67 ]. Given that monitoring lakes to the extent done in the Swedish lakes monitoring program is extremely costly, our results suggest that measuring either phytoplankton or the physicochemical environment may lead to similar results about spatial and temporal variability in the lake landscape; thereby, substantially reducing monitoring costs.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton biodiversity and community structure is largely shaped by water chemistry (particularly nutrients) but can also be influenced by biotic interactions and spatial effects at the inter-basin scale and the resulting spatially structured abiotic lake environment (e.g. [ 67 ]). Therefore, there is high complexity mediating community dynamics that is difficult to scrutinize; accordingly, at this stage, we can only speculate about likely effects of biotic interactions influencing phytoplankton in a way to potentially explain the increasing decoupling over time.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high concentration of lakes in the southern Brazilian Coastal Plain (Schäfer et al, 2009(Schäfer et al, , 2013(Schäfer et al, , 2017 and the high dispersal ability of most macroinvertebrate taxa (e.g. insects; Heino et al, 2015), our assumption was that the set of environmental factors would be the main driver of macroinvertebrate assemblages by potentially filtering out species unable to tolerate specific ranges of environment variables (Tolonen et al, 2020). Because previous studies showed that water chemistry variables of shallow freshwater lakes in the region were related to lake morphometry (Schäfer et al, 2017), we expected that macroinvertebrate richness and composition would be jointly affected by lake morphometry and water chemistry variables.…”
Section: Spatial Factors Such As Geographic Isolation Among Lakes And/mentioning
confidence: 99%
“…Environmental variables associated with morphometry (size, depth and shape) and water chemistry (e.g. nutrient content, water temperature, pH, turbidity, conductivity and dissolved oxygen) of lakes play an important role in structuring macroinvertebrate assemblages (Cai et al., 2019; Heino et al., 2015; Stendera et al., 2012; Tonkin et al., 2017) and directly influence organism composition by affecting their physiology or establishment (Tolonen et al., 2020) and eventually affect biotic interactions (Brucet et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations also were in winter under ice cover (maximum 11.00 µg l -1 ) because there is an internal nutrient supply, especially phosphorus which may increase under anoxic conditions in winter [29]. Value of pH was typical for Latvian lakes (average pH 7.45), only in winter under ice cover average pH was 6.75, and similarly also oxidation reduction potential decreased (average 218 mV), and indicated low oxygen conditions in winter [30]. In common, the hard (average electro conductivity 418 µS cm -1 ) clear-water lakes with such chlorophyll-a concentrations correspond to goodmoderate ecological status [26].…”
Section: A Physico-chemical Parametersmentioning
confidence: 99%